Prediction of the Students' Intention to the Consumption of Soft Drinks: Using the Extended Parallel Process Model - Masoud Karimi; Fatemeh Zare Haroftah; Mohammad Hossein Baghianimoghadam; Vali Bahrevar; Hasan Ghiyasi (Shiraz University of Medical Sciences, 2017)
Background: Soft drinks consumption is a major world public health concern. This study investigates the factors which influence the students' intention to consume fewer amounts of soft drinks, using The Extended Parallel Process Model.Methods: This cross-sectional study was conducted on 320 high schools boys in Yazd, Iran (2014).  A 15-item, 5-point Likert-type scale questionnaire was used to measure the participants' perceived susceptibility, severity, response-efficacy and self-efficacy and intention about soft drinks' consumption. Internal consistency (Cronbach alpha >0.7 for each construct) and external consistency: r = 0.79, P. =0.01) of questionnaire was approved.  Data were analyzed by SPSS 16, using descriptive analysis, bivariate correlation, and stepwise multiple regression analysis. The level of significance was set at 0.05. Results: The participants' average soft drink consumption was 3±3.4 daily glasses. Danger control processes had more frequency over fear control ones (57.7% vs. 42.3% of participants). The intention of fewer amounts soft drinks consumption was positively correlated with perceived response efficacy, self-efficacy and total efficacy. 16% of the participants' intention variations were explained by self-efficacy. The odds of intention towards not to consume soft drinks were significantly higher for the high efficacy/ low threat category (OR=1.51, p= 0.04) compared with low efficacy / low threat category.  Conclusion:The results revealed that inducing fear is not an effective way to promote healthy drinking behavior and the choice of fear appeals is often a poor choice in this subject. It can be suggested that health educators should move from traditional threatening fear arousal messages to improving their target audience's self-efficacy.